The relationship between service quality and effective communication with patient satisfaction in the outpatient installation of Tangerang City Hospital - Damayanty, O.U. Taty; Thaha, Abdul Razak (Science Midwifery, 2025)
Patient satisfaction is a key indicator of the standard of a health facility. Hospitals must be able to provide quality services supported by medical personnel who have competence in the form of effective communication skills. Analyze the relationship between service quality and effective communication with patient satisfaction at the Outpatient Installation of Tangerang City General Hospital. Quantitative method with descriptive research design and cross sectional approach. The sample used was 337 patients, the sampling technique in this study used non probability sampling with a purposive sampling approach. Bivariate data analysis in this study used chi square, while multivariate analysis with multiple logistic regression tests. The results showed that 54.0% of the service quality was good, 49.6% of communication was effective and 58.8% were satisfied with the service at the Tangerang City Hospital Outpatient Installation. All dimensions in the quality of service have a poor presentation of almost 50%. Likewise, the dimension of effective communication has a 50% less effective presentation. The quality of service and effective communication are simultaneously related to patient satisfaction. The most dominant variable related to patient satisfaction in the Outpatient Installation of Tangerang City Hospital was effective communication with an ap value of 0.003 and an OR value of 2.120 (95% CI 1.295-3.470). Service quality and effective communication are associated with patient satisfaction at the Outpatient Installation of Tangerang City General Hospital. Improve responsiveness in the form of response to patient complaints, certainty of service time clearly informed to patients, assurance of reliable medical personnel and empathy to patients, and improve the quality of communication effectively.